Possible Relation between Lack of Posterior Vitreous Detachment and Severe Endogenous Endophthalmitis - Kazuhiko Umazume; Jun Suzuki; Yoshihiko Usui; Yoshihiro Wakabayashi; Hiroshi Goto (Journal of Ophthalmology)
Purpose. Endogenous endophthalmitis (EE) is a rare ocular disease caused by bacterial or fungal infection of intraocular spaces by hematogenous spread of pathogens from distant infectious loci in the body. We investigated the clinical characteristics and management of eyes with EE in ten consecutive patients. Methods. Ten patients (10 eyes) with EE treated at Tokyo Medical University Hospital in 2014 were reviewed. We retrospectively studied the causative organisms, systemic complications, pre/postoperative mean best-corrected visual acuity (BCVA), and status of posterior vitreous detachment (PVD). Results. The 10 patients comprised 8 males and 2 females, with mean age of 71.2 years. The causative organisms were bacteria in 6 eyes and fungi in 4 eyes. Systemic complications included septicemia or disseminated intravascular coagulation in 5 patients and diabetes mellitus in 4 patients. Postoperative BCVA was improved by 0.2log⁡MAR or greater in 4 eyes and decreased in 4 eyes. Vitrectomy was performed in all eyes, and 4 required multiple surgeries. During vitrectomy, PVD was absent in 8 eyes, 4 of which showed retinal necrosis. The mean age of patients with no PVD was 71.2 years. Conclusion. Despite an advanced age, PVD was absent in the majority of patients with EE. PVD may be related to the pathogenesis and aggravation of EE.